KARAKTERISASI FILM TIPIS FEROELEKTRIK ULTRAVIOLET VISIBEL Ba xSr1-xTiO3 DENGAN MENGGUNAKAN TEKNIK SOL-GEL - Ali, Richiy Brantasona Safri Awang; Dewi, Rahmi; Usman, Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The of BaxSr1 -xTiO3 (BST) solution preparation by using of sol-gel technique method has been done. The chemicals used were barium carbonate (BaCO3), strontium carbonate (SrCO3) and titanium oxide (TiO2) with composition x = 0.3; x = 0.2; x = 0.1 in the temperature anealing of 5000C, 5500C and 6000C for 20 minutes. The results obtained from this research is the absorbance spectrum. Samples Ba0,3Sr0,7TiO3, Ba0,2Sr0,8TiO3 and Ba0,1Sr0,9TiO3 at a temperature of 5000C have a wavelength of 438.5 nm and absorbance intensity of 0.1200 a.u. At a temperature of 5500C, the wavelength has 428 nm and absorbance intensity of 0.1261 a.u and at the temperature of 6000C, the wavelength has 435 nm and absorbance intensity of 0.1243 a.u. The greater the wavelength and temperature has the smaller the absorbance value is obtained.